CYBERCRIME AND ECONOMIC DEVELOPMENT IN NIGERIA: CHALLENGES, OPPORTUNITIES, AND STRATEGIC POLICY INTERVENTIONS - John-Williams, Ann Kuro (African Journal of Social and Behavioural Sciences, 2025)
This study examined the implications of cybercrime and economic development in Nigeria. Three research questions and three objectives were formulated to aid the study. The study is anchored on differential association theory propounded by Edwin Sutherland. The study adopted a qualitative research method with the use of desk research methodology; as such data was elicited through Secondary sources such as journals, periodicals, newspaper publications, textbooks and reviews. Our analysis revealed that cybercrime has become a huge menace threatening the socioeconomic and technological advancement of Nigeria as the attention of many youths have been diverted from embarking on productive activities to flamboyant life styles. Also, that the financial losses accrued by consumers and business resulting from the theft of information and money or extortion impedes economic growth. The study concluded that widespread cybercrime has negative impact on the economic development in Nigeria as it tarnishes the image of the country at the global scale. The paper recommends that government should pursue vigorous enlightenment campaigns for the citizens on basic preventive and protective measures against cybercrime.